Characterization of Tigecycline Resistance Among Tigecycline Non-susceptible Klebsiella pneumoniae Isolates From Humans, Food-Producing Animals, and in vitro Selection Assay - Moghimi, Mohaddeseh; Haeili, Mehri; Mohajjel Shoja, Hanieh (Frontiers in Microbiology, 2021)
Emergence of extensively drug resistant isolates of Klebsiella pneumoniae has prompted increased reliance on the last resort antibiotics such as tigecycline for treating infections caused by these pathogens. Consumption of human antibiotics in food production industry has been found to contribute to the current antibiotic resistance crisis. In the current study we aimed to investigate the mechanisms of tigecycline (TGC) resistance among 18 TGC-nonsusceptible (resistant or intermediate) K. pneumoniae (TGC-NSKP) isolates obtained from human (n=5), food animals (n=7) and in vitro selection experiment (n=6). Isolates were genotyped by MLST. The ramR, acrR, rpsJ, tetA and mgrB (for colistin resistance) genes were sequenced. The presence of tetX, tetX1 and carbapenemase genes was examined by PCR. Susceptibility to different classes of antibiotics was evaluated by disc diffusion and broth macrodilution methods. The expression level of acrB was quantified by RT-qPCR assay. The 12 TGC-NSKP isolates (MICs=4-32mg/l) belonged to 10 distinct sequence types including ST37 (n=2), ST11, ST15, ST45, ST1326 (animal isolates), ST147 (n=2, human and animal isolates), ST16, ST377, ST893, ST2935 (human isolates). Co-resistance to TGC and colistin was identified among 57% and 40% of animal and human isolates respectively. All human TGC-NSKP isolates carried carbapenemse genes (blaOXA-48, blaNDM-1, blaNDM-5). The tetX/X1 genes were not detected in any isolates. About 88% of TGC-NSKP isolates (n=16) carried ramR or acrR alterations including missense/nonsense mutations (A19V, L44Q, I141T, G180D, A28T, R114L, T119S, Y59stop, Q122stop), insertions (positions +205, +342) or deletions (position +205) for the ramR, and R90G substitution or frameshift mutations for AcrR. Among 7 colistin resistant isolates, 5 harbored inactivated/mutated MgrB due to premature termination by nonsense mutations, insertion of IS elements and frameshift mutations. All isolates revealed wild-type RpsJ and TetA (if present). Increased expression of acrB gene was detected among all resistant isolates with the in vitro selected mutants showing the highest values. A combination of RamR and AcrR alterations were involved in TGC non-susceptibility in the majority of studied isolates.